Pengaruh Kualitas Pelayanan dan Tarif Pajak Terhadap Penggelapan Pajak - Desma Ramadhan; Septian Arief Budiman (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effect of service quality and tax rates on tax evasion among individual taxpayers at KPP Pratama Serpong. A quantitative approach with multiple linear regression was applied using questionnaire data from 100 respondents. The results show that service quality has a significant negative effect on tax evasion, meaning that better tax authority services reduce taxpayers’ tendency to evade taxes. Conversely, tax rates have a significant positive effect, where higher or burdensome rates increase the likelihood of evasion. Simultaneously, service quality and tax rates significantly influence tax evasion, contributing 22.5% to its variation. These findings highlight the importance of improving service quality and applying fair tax rates to minimize tax evasion practices.